Morfologia de la planta de frijol comun - Debouck, Daniel G.; Hidalgo, R. (United Nations Development Programme, 1985)
The morphology of the different parts of the bean plant (roots, stems, branches and axillary complexes, leaves, inflorescences, flowers, fruits, and seeds) is described. The growth habits and floral and vegetative development of beans are described and illustrated. (CIAT)